Modeling and optimization of palm oil moisture loss as biodiesel pretreatment. Issue 1 (February 2020) - Hendrawan, Y; Maharani, N S; Argo, B D; Wibisono, Y
Abstract: One solution to the problem of energy that can be used as a substitute for fuel oil is biodiesel. Palm oil can be used as biodiesel raw material. The advantage of palm oil is its sustainable availability. However, the water content of palm oil still cannot meet the biodiesel quality requirements based on ASTM D975-08a and ASTM D6751-12 which is less than 0.05%. The purpose of this study is to model and optimize the concentration of zeolite and adsorption times to decrease water content in palm oil. The method in this research is to use activated zeolite adsorption. Data from the results of water loss in palm oil as a pretreatment in the manufacture of biodiesel will be processed using response surface methodology (RSM) with the central composite design (CCD) so that a model and optimum point of zeolite concentration and adsorption time can be found. The model produced using the response surface methodology (RSM) method with a central composite design (CCD) design in the form of quadratic equations. The optimization results produce an optimum value of water loss of 2.74% with an error rate of 4.20%. This optimum value is achieved by zeolites concentration of 13.20% and adsorption time of 126.11 minutes.